AN ANALYSIS OF ADJACENCY PAIRS ON CONVERSATION IN BLACK PANTHER MOVIE - Pardede, Nova Lina; Herman, Herman; Silalahi, Dumaris E. (Universitas Sebelas Maret, 2021)
This research investigated about adjacency pairs in conversation of the Black Panther movie from five main characters in the movie. This research used qualitative research by applied content analysis as a research design. The data obtained from transcript of Black Panther movie which has 134 minutes duration. The researchers transcribed the data in written form and analyzed by using theory of adjacency pairs. The researchers found 71 data of the conversation five main characters in the movie. Based on the research, there are 71 data of conversation that consist of thirteen types of adjacency pairs. From 71 data of conversation, there are 2 pairs of greeting-greeting sequence, 2 pairs of summons-answer sequence, 2 pairs of apology-minimization sequence, 24 pairs of question-answer sequence, 2 pairs of request-acceptance/refusal sequence, 4 pairs of offer-acceptance/refusal sequence, 2 pairs of blame-admission/denial sequence, 3 pairs of invitation-acceptance/refusal sequence, 8 pairs ofÂ assessment-agreement/disagreement sequence, 11 pairs of commands-compliance/incompliance sequence, 2 pairs of suggestion-acceptance/refusal sequence, 3 pairs of assertion-agreement/disagreement sequence and 6 pairs of announcement-acknowledgement sequence. From the research finding it can be concluded that question-answer was mostly-appeared type of adjacency pairs in the conversation by five main characters in the movie